2020
DOI: 10.1177/2473011420930691
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes and Early Complications After Synthetic Cartilage Device Implantation

Abstract: Background: Previous Level I studies show promising results for the use of a hydrogel synthetic cartilage implant (SCI) for the treatment of hallux rigidus. A recent independent retrospective review has put those results into question, however. The purpose of this article is to report patient-reported outcomes and early complications using this implant so as to add to the paucity of data in the literature regarding this implant. Methods: This was a retrospective chart review of patients undergoing hydrogel syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This study found that 55% of patients were still experiencing pain at the final follow-up. The success of SCI surgery in reducing pain from baseline is well founded with reports of significant improvement in PROMIS pain interference/intensity [ 20 ], VAS [ 11 , 21 , 25 ], and MOXFQ [ 24 ] scores from as early as six weeks post-surgery. However, despite these significant improvements, a plethora of studies still report patients experience persistent pain [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that 55% of patients were still experiencing pain at the final follow-up. The success of SCI surgery in reducing pain from baseline is well founded with reports of significant improvement in PROMIS pain interference/intensity [ 20 ], VAS [ 11 , 21 , 25 ], and MOXFQ [ 24 ] scores from as early as six weeks post-surgery. However, despite these significant improvements, a plethora of studies still report patients experience persistent pain [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found a total revision rate to arthrodesis of 8.7% due to reduced joint space with implant degeneration and a stress fracture causing subsidence and valgus drift. The short-term revision rate varied considerably in the literature from 1.9% [ 20 ] to 16.9% [ 21 ] within two years, increasing to 27.8% when considering only symptomatic patients (Table 4 ) [ 15 ]. In the largest multicenter randomized controlled trial, Baumhauer et al reported a revision rate of 9.2% within two years due to persistent pain of unknown cause [ 11 ].…”
Section: Discussionmentioning
confidence: 99%